A Boron‐Fluorinated Tris(pyrazolyl)borate Ligand (FTp*) and Its Mono‐ and Dinuclear Copper Complexes [Cu(FTp*)2] and [Cu2(FTp*)2]: Synthesis, Structures, and DFT Calculations. Issue 23 (23rd April 2016) - Augenstein, Timo; Dorner, Franziska; Reiter, Kevin; Wagner, Hanna E.; Garnier, Delphine; Klopper, Wim; Breher, Frank
Abstract: Reaction of [Si(3, 5‐Me2 pz)4 ] (1 ) with [Cu(MeCN)4 ][BF4 ] (2 ) gave the mono‐ and dinuclear copper complexes [Cu2 ( F Tp*)2 ] (3 ) and [Cu( F Tp*)2 ] (4 ). Both complexes contain the so‐far unprecedented boron‐fluorinated F Tp* ligand ([FB(3, 5‐Me2 pz)3 ] − with pz=pyrazolyl) originating from1, acting as a pyrazolyl transfer reagent, and the [BF4 ] − counter anion of2, serving as the source of the BF entity. The solid‐state structures as well as the NMR and EPR spectroscopic characteristics of the complexes were elaborated. Pulsed gradient spin echo (PGSE) experiments revealed that3 retains (almost entirely) its dimeric structure in benzene, whereas dimer cleavage and formation of acetonitrile adducts, presumably [Cu( F Tp*)(MeCN)], is observed in acetonitrile. The short Cu⋅⋅⋅Cu distance of 269.16 pm in the solid‐state is predicted by DFT calculations to be dictated by dispersion interactions between all atoms in the complex (the Cu−Cu dispersion contribution itself is only very small). As revealed by cyclic voltammetry studies, 3 shows an irreversible (almost quasi‐reversible at higher scan rates) oxidation process centred at E pa =−0.23 V ( E 0 1/2 =−0.27 V) (vs. Fc/Fc + ). Oxidation reactions on a preparative scale with one equivalent of the ferrocenium salt [Fc][BF4 ] (very slow reaction) or air (fast reaction) furnished blue crystals of the mononuclear copper(II) complex [Cu( F Tp*)2 ] (4 ). As expected for a Jahn–Teller‐active system, the coordination sphere around copper(II) is strongly distorted towards a stretched octahedron, in accordance with EPR spectroscopic findings. Abstract : Fluorinated at boron : The mono‐ and dinuclear copper complexes [Cu II ( F Tp*)2 ] and [Cu I 2 ( F Tp*)2 ] containing the so‐far unprecedented boron‐fluorinated tris(pyrazolyl)borate ligand ( F Tp*) are reported. The short Cu⋅⋅⋅Cu distance in [Cu I 2 ( F Tp*)2 ] was predicted by DFT‐D3 calculations to be dictated by dispersion interactions between all atoms in the complex, whereas the Cu–Cu dispersion contribution itself is only very small.